The Influence of Fear of Missing Out as the Mediating Variable against Purchase Decision - Permana, Dudi; Abiyyah, Hana Natania; Hokroh, Mohammed (ARE Publisher, 2025)
Objectives: This research aims to analyze the effects of Perceived Scarcity and Social Anxiety on Purchase Decision with FoMO as a mediation variable in the context of McDonald’s limited-edition products.Methodology: A sample of 105 consumers who had purchased these products was used for the study, with data collected through questionnaires. The analysis was carried out using statistical techniques like SEM-PLS.Findings: The results show no mediation. No mediation assumes that the independent variable does not have a mediator effect or intermediary variable on the interaction between the independent variable and the dependent variable. So in this study, the FoMO variable does not mediate the relationship between variables X and Y which is indicated by the results being rejected or not significant.Conclusion: The results in this study indicate that (1) FoMO (Fear of Missing Out) has a negative and insignificant effect on Purchase Decision, (2) Perceived Scarcity has a positive and significant effect on FoMO (Fear of Missing Out), (3) Perceived Scarcity has a positive and significant effect on Purchase Decision, (4) Social has a positive and significant effect on FoMO (Fear of Missing Out, (5) Social Anxiety has a positive and significant effect on Purchase Decision, (6) FoMO (Fear of Missing Out) has a negative and insignificant effect in mediating the influence of Perceived Scarcity on Purchase Decision, (7) FoMO (Fear of Missing Out) has a negative and insignificant effect in mediating the influence of Social Anxiety on Purchase Decision.